The Broken Bridge of Collaboration: Unpacking Poverty Politics in Eastern Indonesia - Onga, Fiko; Handoko, V. Rudy; Maduwinarti, Ayun (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study investigates the implementation of Collaborative Governance in poverty alleviation programs in Bolaang Mongondow Timur Regency, North Sulawesi. Grounded in a constructivist paradigm, the research adopts a qualitative case study approach. Data were collected through in-depth interviews, observations, document analysis, and focus group discussions involving stakeholders from five key sectors: government, business, academia, civil society, and media. The findings reveal that although a formal structure (TKPKD) has been established to facilitate coordination, its effectiveness has been compromised following the issuance of Presidential Regulation No. 163/2024, which dissolved the existing institutional framework without providing operational guidelines for its replacement (BPPK). The study identifies a paradox of collaboration: formal documents and coordination mechanisms exist, yet genuine multi-actor interaction remains limited. The involvement of non-government actors is mainly instrumental and symbolic, with civil society and media often excluded from meaningful deliberation. The research concludes that Collaborative Governance in the region remains characterized by a top-down administrative logic rather than an inclusive, transformative practice. A key recommendation is the institutionalization of regular, deliberative, and open multi-actor forums supported by accurate and transparent data systems. This study contributes theoretically by offering a localized adaptation of the Pentahelix model, enriched by institutional improvisation and contextual wisdom.